Analisis Kinerja Turbin Pelton Proto X dengan Varian Ukuran Nosel Menggunakan Aplikasi CFD - Yusrizal Yusrizal; Ayu Amanah; Bagas Prasetio (Fakultas Teknik - Universitas Bung Karno, 2023)
After get trial of performance of Turbin Pelton Proto X was done with some variations of desain such as percentage of valve opening, nozel distance from center of runner and nozel diameter than get the result of performance. To complete and get perfection need to do simulation and analyse Computational Fluid Dynamic (CFD) uses powerfull engineering software. Based on turbin Pelton Proto X performance result, the velocity of flow is 1.74 m/s. This value will be use for fill parameter conditions when Ansys Fluent is setting up. For this case, it will simulate and analyse of turbin Pelton Proto X with different nozzle diameter and than know the type of flow happen in system of turbin Pelton piping. The result of this CFD analyzing can also give recommendations for development of turbin Pelton Proto X to get higher performance.